Socrates and the Problem of Personality Formation - Rickevičiūtė, Kristina (Problemos, 1968)
The article aims at pointing out those features of Socrates’ character and teaching which bear a relation to the forming of personality. Xenophon’s, Plato’s, Aristotle’s, Diogenes Laertius’ and other writers’ works are investigated for data. The stress is laid upon the formation of general ethic concepts by means of definition and the induction method, applied by Socrates. The author points out that though Socrates’ principles of ethics were limited by the economical-political conditions and the level of the development of science at that time, his demand of acting on the basis of precise knowledge is of importance even nowadays.